V˙ O 2 kinetics and energy contribution in simulated maximal performance during short and middle distance-trials in swimming - Almeida, Tiago A. F. [UNESP]; Pessôa Filho, Dalton M. [UNESP]; Espada, Mário A. C.; Reis, Joana F.; Simionato, Astor R. [UNESP]; Siqueira, Leandro O. C. [UNESP]; Alves, Francisco B. (Springer Nature, 2020)
Purpose: This study aims to analyze swimmers’ oxygen uptake kinetics (V˙ O 2K) and bioenergetic profiles in 50, 100, and 200 m simulated swimming events and determine which physiological variables relate with performance. Methods: Twenty-eight well-trained swimmers completed an incremental test for maximal oxygen uptake (Peak-V˙ O 2) and maximal aerobic velocity (MAV) assessment. Maximal trials (MT) of 50, 100, and 200-m in front crawl swimming were performed for V˙ O 2K and bioenergetic profile. V˙ O 2K parameters were calculated through monoexponential modeling and by a new growth rate method. The recovery phase was used along with the blood lactate concentration for bioenergetics profiling. Results: Peak-V˙ O 2 (57.47 ± 5.7 ml kg−1 min−1 for male and 53.53 ± 4.21 ml kg−1 min−1 for female) did not differ from V˙ O 2 peak attained at the 200-MT for female and at the 100 and 200-MT for male. From the 50-MT to 100-MT and to the 200-MT the V˙ O 2K presented slower time constants (8.6 ± 2.3 s, 11.5 ± 2.4 s and 16.7 ± 5.5 s, respectively), the aerobic contribution increased (~ 34%, 54% and 71%, respectively) and the anaerobic decreased (~ 66%, 46% and 29%, respectively), presenting a cross-over in the 100-MT. Both energy systems, MAV, Peak-V˙ O 2, and V˙ O 2 peak of the MT’s were correlated with swimming performance. Discussion: The aerobic energy contribution is an important factor for performance in 50, 100, and 200-m, regardless of the time taken to adjust the absolute oxidative response, when considering the effect on a mixed-group regarding sex. V˙ O 2K speeding could be explained by a faster initial pacing strategy used in the shorter distances, that contributed for a more rapid increase of the oxidative contribution to the energy turnover.
Keywords: Energy system contribution; Maximal trials; Oxygen uptake kinetics; Rate of adjustment of V˙ O 2; Swimming